Carbohydrate Sulfotransferase 4 Inhibits the Progression of Hepatitis B Virus-Related Hepatocellular Carcinoma and Is a Potential Prognostic Marker in Several Tumors - Zhang, Longshan; Fan, Yao; Wang, Xiaoqing; Yang, Mi; Wu, XiXi; Huang, Weiqiang; Lan, Jin; Liao, Liwei; Huang, Wenqi; Yuan, Lu; Pan, Hua; Wu, Yuting; et al. (Frontiers in Oncology, 2020)
CHST4 plays an important role in lymphocyte homing and is abnormally expressed in several cancer types; however, its precise function in tumor development and progression is unknown. Here we confirm that CHST4 is aberrantly expressed in various tumor subtypes. In particular, we found CHST4 expression was downregulated in hepatitis B virus-related hepatocellular carcinoma (HBV-HCC) tumors compared to paired normal tissue. We also showed CHST4 overexpression inhibited the proliferation and metastasis of HCC cells in vitro. Clinically, CHST4 was identified as an independent prognostic factor for HBV-HCC patients. We further illuminated the anti-tumor role and mechanism of CHST4 in HBV-HCC by constructing a FENDRR-miR-10b-5p-CHST4 competing endogenous RNA network. We found downregulation of CHST4 expression may promote HBV expression and regulate ribonucleoprotein complex biogenesis to promote malignant behaviors in HBV-HCC. CHST4 may also recruit CD4+ T cells, macrophages, dendritic cells, and neutrophils into the tumor microenvironment to inhibit the progression of HBV-HCC. Overall, our findings suggest that CHST4 acts as a tumor suppressor in HCC-HBV, and represents a potential diagnostic and therapeutic target.